Encounters in magnetic resonances : (World Scientific, 1996)
This book presents a selection of papers, written by Nicolaas Bloembergen and his associates during the years 1946-1962, on the subjects of nuclear magnetic relaxation, paramagnetic relaxation and masers, and magnetic resonance spectroscopy of solids. The volume begins with autobiographical notes to provide a personal historical background. Each paper is preceded by commentary with additional information regarding the early development of magnetic resonance in condensed matter.